2022
DOI: 10.1002/advs.202203351
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Solution of Smart Supramolecular Peptides to Capture Semaphorin 4D against Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of vision loss in working age population. Intravitreal injection of anti‐VEGF antibody is widely used in clinical practice. However, about 27% of patients show poor response to anti‐VEGF therapy and about 50% of these patients continue to have macular thickening. Frequent intravitreal injections of antibody may increase the chance of endophthalmitis and cause visual loss or even blindness once happened. Therefore, there is a greatly urgent need for novel noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…4D binding to the three receptors, achieving a significant reduction in pathologic retinal neovascularization and leakage. What's more, this study confirmed that in DR treatment, non-invasive SSP eye drops can achieve the same therapeutic effect as invasive antibody injections, when SSP eye drops combined with anti-VEGF can increase the current clinical therapeutic effect by 50% (154). Curcumin (CUR) and many other plant-derived polyphenolic compounds are known to act on multiple signaling pathways simultaneously; however, most of them have low bioavailability after oral administration, resulting in poor clinical efficacy.…”
Section: Other Nano-delivery Technologiessupporting
confidence: 72%
See 1 more Smart Citation
“…4D binding to the three receptors, achieving a significant reduction in pathologic retinal neovascularization and leakage. What's more, this study confirmed that in DR treatment, non-invasive SSP eye drops can achieve the same therapeutic effect as invasive antibody injections, when SSP eye drops combined with anti-VEGF can increase the current clinical therapeutic effect by 50% (154). Curcumin (CUR) and many other plant-derived polyphenolic compounds are known to act on multiple signaling pathways simultaneously; however, most of them have low bioavailability after oral administration, resulting in poor clinical efficacy.…”
Section: Other Nano-delivery Technologiessupporting
confidence: 72%
“…4D binding to the three receptors, achieving a significant reduction in pathologic retinal neovascularization and leakage. What’s more, this study confirmed that in DR treatment, non-invasive SSP eye drops can achieve the same therapeutic effect as invasive antibody injections, when SSP eye drops combined with anti-VEGF can increase the current clinical therapeutic effect by 50% ( 154 ).…”
Section: Drug-delivery Systemsupporting
confidence: 69%
“…Furthermore, other studies have demonstrated that either genetic disruption of Sema4D/PlexinB1 or pharmacological inhibition of Sema4D significantly mitipathological retinal angiogenesis and vascular leakage in the oxygen-induced retinopathy model, as well as reduced pericyte loss in the streptozotocin-induced diabetes model. 29,41 Meanwhile, they also observed no significant difference in retinal vascular development between Sema4D-KO mice and their littermate WT mice. 29 Our current study revealed that Sema4D is highly expressed in macrophages within CNV lesions and plays a significant role in regulating pathological neovascularization and leakage.…”
Section: Discussionmentioning
confidence: 94%
“…Accumulating evidence has highlighted the importance of Sema4D and its downstream RhoA/ROCK pathway in the occurrence and progression of multiple neovascular diseases, including DR, 29 , 41 whereas their roles in neovascular AMD have not yet been elucidated. Herein, we reported that Sema4D mRNA and protein expression were significantly elevated over time in a laser-induced CNV model, especially in aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sema4D can be proteolytic cleaved into its soluble form (sSema4D) and then shed from the cell surface. The level of sSema4D is significantly upregulated in the vitreous humor of patients with DR comparing to that in patients with macular hole, as well as upregulated in streptozotocin-induced mouse DR model [ 242 ]. The aqueous sSema4D, a strongly pro-angiogenesis and permeable factor, was reported to be positively correlated with the central subfield thickness in patients with DR [ 242 ].…”
Section: Altered Cytokines and Signaling Pathways Involved In Microva...mentioning
confidence: 99%